1999
DOI: 10.1590/s0100-204x1999001200013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de linhagens, híbridos F1 e cultivares de pimentão quanto à resistência a Meloidogyne spp.

Abstract: RESUMO -Com o objetivo de avaliar híbridos F 1 de pimentão, juntamente com suas linhagens progenitoras e cultivares, quanto à resistência a Meloidogyne incognita (raças 1, 2, 3 e 4) e a M. javanica, foi instalado um experimento em casa de vegetação nas dependências da Pioneer Sementes Ltda, em Ijaci, MG. Foi utilizado o delineamento de blocos casualizados, em esquema de parcela subdividida, com cinco parcelas (compostas pelas quatro raças de M. incognita e mais a espécie M. javanica) e 48 subparcelas (composta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Regarding RI, this cultivar showed a susceptible reaction to M. incognita race 3 and M. enterolobii and was highly resistant to M. javanica (Table 3). Peixoto et al (1999) also observed a susceptible reaction to M. incognita race 3 and resistance to M. javanica for 'Ikeda' when evaluating different genotypes of sweet pepper. Bitencourt and Silva (2010), Melo et al (2011), andGoncalves et al (2014) also observed susceptibility of 'Ikeda' to M. enterolobii.…”
Section: Resultsmentioning
confidence: 81%
“…Regarding RI, this cultivar showed a susceptible reaction to M. incognita race 3 and M. enterolobii and was highly resistant to M. javanica (Table 3). Peixoto et al (1999) also observed a susceptible reaction to M. incognita race 3 and resistance to M. javanica for 'Ikeda' when evaluating different genotypes of sweet pepper. Bitencourt and Silva (2010), Melo et al (2011), andGoncalves et al (2014) also observed susceptibility of 'Ikeda' to M. enterolobii.…”
Section: Resultsmentioning
confidence: 81%
“…Peixoto et al (1999) report that preventive measures are the most effective in controlling these phytoparasites. These include crop rotation, use of plants toxic to nematodes, soil solarization and application of chemical products.…”
Section: Key-wordsmentioning
confidence: 99%
“…Biber yetiştiriciliğinin yapıldığı alanlarda M. incognita'nın yaygın olduğu bilinmektedir. M. incognita biberde üreyip zarar verirken, M. javanica biberde üreyemez ve zarar veremez (Hartman & Sasser, 1985;Peixoto et al, 1997;Özarslandan & Elekcioğlu, 2003). Sebze alanlarında kök-ur nematodları ile mücadelede genellikle fumigant etkili nematisitler kullanılmaktadır.…”
Section: Introductionunclassified